The impact of adopting the Kaizen Strategy on empowering human resources in the bank of agriculture and rural development - Adjemi, Sara; Sahnoune, Hiba; Meliani, Choukri (International journal of economic perspectives, 2025)
This study aims to measure the impact of adopting the Kaizen strategy on empowering human resources in the Bank of Agriculture and Rural Development in Eastern Algeria (Annaba, Eltaref). To achieve the study's objectives, 39 questionnaires were analyzed using the advanced statistical software SPSS.v26.The study revealed a statistically significant effect of each dimension of Kaizen strategy on empowering human resources in the bank under study, which achieves an improvement and increase in the degree of empowering human resources by adopting the dimensions of the Kaizen strategy and implementing everything planned by forming specialized work teams and in a spirit of cooperation and assistance among team members to reach the required level, and correcting the deviations that were discovered.